ANALISIS PUSAT-PUSAT PERTUMBUHAN EKONOMI DI KABUPATEN SEKADAU PROVINSI KALIMANTAN BARAT - MASIUN, STEFANUS (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT A regional development indeed, is aimed at lifting the quality of lives of the society within the region through integrated and proper of sectors and spatial development. An effective and efficient development planning should take into account macro, sectoral and regional development planning harmoniously. At the same time, a good economic development planning will determine qualified economic growth, reducing poverty, creating more jobs and reducing inter region disparities. This is the context of this thesis research. This research analyzed sub-district basis economic growth centers in Sekadau District of West Kalimantan through sub district based. As a new district, Sekadau District is hoped to bring significant impacts especially on public service sector and better welfare for every member of society. To reach the goal, economic development is one of the strategies to be done. Through creating economic growth centers in the region, will enhance the economic growth of the hinterlands. Sekadau district consists of 7 sub districts. The sub districts are Nanga Mahap, Nanga Taman, Sekadau Hulu, Sekadau Hilir, Belitang Hilir, Belitang andn Belitang Hulu. The main data analyzed in this research are economic, social and government facilities in every sub district. The analysis tools applied are Scalogram, Geographic Information System (GIS) and Interaction Analysis. The findings of the research show that Sekadau Hilir is the main economic growth center of Sekadau. The total numbers of economic, social and government facilities are 738. It is the first economic order of Sekadau. In the Southern part, Nanga Taman is the economic growth center within the area with 257 facilities. While in the Northern part, the growth center is Belitang Hilir with 223 facilities. Because of central and Strategic position of Sekadau Hilir, other sub districts consequently, are the hinterlands of Sekadau Hilir. Through interaction analysis, it is known that Sekadau Hilir is the main center of interaction of people, goods and services. It is understandable, Sekadau Hilir, especially Sekadau Town, is the capital town of Sekadau district. The people from all sub districts come to Sekadau town mainly for shopping, education, health care, and government business. Even though, from the research finding, it is clearly founded that there are economic disparities among three main zones within the district. Center area, Sekadau Hilir, is the most provided by economic, social and government facilities more than three sub districts in the South. The worse is three sub districts in the North, less facilities provided compared with those in the South. The lagging zone of economic, social and government facilities in the district is in the North.***